Ответы и объяснения

2013-04-25T16:25:24+00:00

Fe-Fe2O3-FeCL3-Fe(OH)3-Fe2O3-Fe

1) 4Fe + 3O2 = 2Fe2O3

2) Fe2O3 + 6HCl = 2FeCl3 + 3H2O

3) FeCl3 + 3NaOH = 3NaCl + Fe(OH)3 (осадок, стрелка вниз)

4) 2Fe(OH)3 = (t ) Fe2O3 + 3H2O

5) Fe2O3 + 3H2 = 2Fe + 3H2O

 

Mg-MgO-Mg(NO3)2-Mg(OH)2-MgO-MgSO4

1) 2Mg + O2 = 2MgO

2) MgO + 2HNO3= Mg(NO3)2 + H2O

3) Mg(NO3)2 + 2NaOH = 2NaNO3 + Mg(OH)2 (осадок, стрелка вниз)

4) Mg(OH)2 = MgO + H2O

5) MgO + SO3 = MgSO4

Лучший Ответ!
2013-04-25T16:27:19+00:00

Fe(NO3)3 + 3KOH = Fe(OH)3 + 3KNO3 
2Fe(OH)3 нагреваем = Fe2O3 + 3H2O 
Fe2O3 + 3H2 = 2Fe + 3H2O 

В последнем - наверно, FeCl3?
2Fe + 3Cl2 = 2FeCl3 

Если FeCl2:

Fe + 2HCl(разбавленный) = FeCl2 + H2↑